2008
DOI: 10.1016/j.intell.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive cascade in infancy: Pathways from prematurity to later mental development

Abstract: Using data from a longitudinal study of preterms and full-terms, the present study examined the structure of infant cognition at 12 months, the extent to which five 12-month abilities (attention, speed, recognition, recall, and representational competence) mediated the relation from prematurity to mental development at 2 -3 years, and how continuity and change in infant information processing from 7 to 12 months affected later outcome. The results indicated that 12-month measures of infant information processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
101
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 71 publications
15
101
0
1
Order By: Relevance
“…They report that the development of infants aged 6-12 months (measured by attention to novelty) is significantly correlated at 0.34 with IQ at the age of 3 years, and at 0.26 (0.53 corrected for unreliability) with IQ at the age of 21 years, while IQ at the age of 3 years is correlated at 0.70 with IQ at the age of 21 years. In another recent study it has been shown that the development of infants aged 12 months (measured by attention to novelty and imitation) is significantly correlated at between 0.19 and 0.35 with Bayley Mental Development at the ages of 2 and 3 years (Rose, Feldman, Jankowski, & van Rosssem, 2008). Thus, numerous have confirmed that there are positive correlations between the DQs of infants, the IQs of preschool children, and the IQs of older children and adults.…”
Section: Positive Correlations Between Dqs and Iqsmentioning
confidence: 80%
“…They report that the development of infants aged 6-12 months (measured by attention to novelty) is significantly correlated at 0.34 with IQ at the age of 3 years, and at 0.26 (0.53 corrected for unreliability) with IQ at the age of 21 years, while IQ at the age of 3 years is correlated at 0.70 with IQ at the age of 21 years. In another recent study it has been shown that the development of infants aged 12 months (measured by attention to novelty and imitation) is significantly correlated at between 0.19 and 0.35 with Bayley Mental Development at the ages of 2 and 3 years (Rose, Feldman, Jankowski, & van Rosssem, 2008). Thus, numerous have confirmed that there are positive correlations between the DQs of infants, the IQs of preschool children, and the IQs of older children and adults.…”
Section: Positive Correlations Between Dqs and Iqsmentioning
confidence: 80%
“…In infancy, attention was assessed through measuring look duration and shift rate (Rose, Feldman, & Jankowski, 2009;Rose, Feldman, Jankowski, & Van Rossem, 2008). For children older than 3 years and adolescents, attention was most commonly assessed through tasks, such as the Attention Sustained Test, Test of Everyday Attention, and Continuous Performance Tasks, which require individuals to find targets in a display of nontargets as quickly as possible (selective attention) or to work on a task for an extended period (sustained attention; Bayless & Stevenson, 2007;Caravale et al, 2005Caravale et al, , 2012Cserjesi et al, 2012;Mulder, Pitchford, Hager, & Marlow, 2009;Mulder, Pitchford, & Marlow, 2011;Odd et al, 2012).…”
Section: Attentional Controlmentioning
confidence: 99%
“…For children older than 3 years and adolescents, attention was most commonly assessed through tasks, such as the Attention Sustained Test, Test of Everyday Attention, and Continuous Performance Tasks, which require individuals to find targets in a display of nontargets as quickly as possible (selective attention) or to work on a task for an extended period (sustained attention; Bayless & Stevenson, 2007;Caravale et al, 2005Caravale et al, , 2012Cserjesi et al, 2012;Mulder, Pitchford, Hager, & Marlow, 2009;Mulder, Pitchford, & Marlow, 2011;Odd et al, 2012). Preterm-born children consistently show poorer selective attention and sustained attention across all gestational ages (Bayless & Stevenson, 2007;Caravale et al, 2005Caravale et al, , 2012Cserjesi et al, 2012;Hallin, Hellstrom-Westas, & Stjernqvist, 2010;Mulder et al, 2009;Nosarti et al, 2007;Rose et al, 2008Rose et al, , 2009Shum, Neulinger, O'Callaghan, & Mohay, 2008;Woodward, Clark, Pritchard, Anderson, & Inder, 2011). Preterm-born children appeared to experience greater difficulty in identifying stimuli and using a search strategy, and were therefore less able to stay focused on one task (Woodward et al, 2011).…”
Section: Attentional Controlmentioning
confidence: 99%
“…Second, the measures of infant information processing involved are believed to mediate the relation between birth status and later cognition. Using data from a longitudinal study of PT and FT, their study (Rose, et al, 2008) evidenced how 12-month abilities (attention, processing speed, recognition, recall, and representational competence) mediated the relation between prematurity and mental development at 2-3 years, and how continuity and change in infant information processing from 7 to 12 months affected later outcome. The results indicated that two further basic abilities (attention and processing speed) influenced the more complex ones, which in turn influenced later cognition.…”
mentioning
confidence: 99%
“…In this view, pre-term birth can determine the loss of efficiency in some basic abilities or processes which influence the final outcome of language development. More specifically, Rose, et al ( , 2008 proposed a model of infant cognition which puts forth two central tenets. First, infant cognition is posited to be characterized by a cognitive cascade in which more fundamental or basic abilities underpin more complex ones that, in turn, influence general intelligence.…”
mentioning
confidence: 99%